The role of soil ecosystem services in the circular bioeconomy - Anikwe, M. A. N.; Ife, K (Frontiers in Soil Science, 2023)
The concept of a circular bioeconomy focuses on the sustainable use of biological resources, minimizing waste and negative environmental impacts. Soil ecosystem services are crucial in this context as they support agricultural production, biodiversity conservation, and nutrient recycling. The circular bioeconomy offers benefits like resource efficiency, reduced waste, lower environmental impacts, and economic opportunities, with soil ecosystem services playing a significant role in achieving these benefits. Soil provides various services for human well-being, including security, protection from ecological shocks, access to balanced diets, clean water, clean air, and energy for temperature control. This review highlights the importance of soil ecosystem services in circular resource management and biobased sustainable production systems. These services encompass provisioning, regulating, cultural, and supporting roles, providing resources like food, fibre, and fuel, controlling erosion and temperature, offering aesthetic value, and sustaining plant and animal diversity. The bioeconomy comprises knowledge, research, technology, and innovation related to biological resource production, use, conservation, and regeneration. The application of circular bioeconomy strategies benefits from the ecological services soil provides to bio-based industries. The policy that converts farming, grazing, and woodland systems into renewable operations is bound to protect soil functions while relieving pressure on other critical ecosystem functions. Overall, a holistic understanding of soil ecosystem services is crucial for successfully implementing circular practices across different bioeconomy sectors. Soil conservation, sustainable management, and the protection of soil resources are vital for maintaining the services that support a circular bioeconomy.